Pengaruh Total Quality Management Dan Reward Terhadap Kinerja Manajerial Pada PT. Cahaya Mas Utama - Ramadhan Priyana; Johan Maulana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to analyze the effect of Total Quality Management (TQM) and Reward on Managerial Performance at PT. Cahaya Mas Utama. The background of this research is based on the importance of improving managerial performance as a strategic factor in achieving organizational goals effectively and sustainably. In facing increasingly competitive business conditions, companies are required to implement integrated quality management principles as well as reward systems that are able to motivate managers to perform their managerial functions optimally. This study employs a quantitative approach using a survey method. Primary data were collected through the distribution of questionnaires to 65 managerial respondents at PT. Cahaya Mas Utama. The data were analyzed using multiple linear regression analysis, with hypothesis testing conducted through simultaneous testing (F-test) and partial testing (t-test), as well as the coefficient of determination to measure the contribution of the independent variables to the dependent variable. The results of the study indicate that Total Quality Management and Reward simultaneously have a significant effect on Managerial Performance. This is evidenced by a significance value of 0.000 (< 0.05) and an F-value of 25.589, indicating that the combined implementation of quality management and reward systems significantly enhances managerial performance. Partially, Total Quality Management has a positive and significant effect on Managerial Performance, with a significance value of 0.000 (< 0.05) and a positive regression coefficient, indicating that better implementation of TQM principles leads to higher levels of managerial performance.